Bioavailability of Nutritional Resources From Cells Killed by Oxidation Supports Expansion of Survivors in Ustilago maydis Populations - Milisavljevic, Mira; Petkovic, Jelena; Samardzic, Jelena; Kojic, Milorad (Frontiers in Microbiology, 2018)
After heavy exposure of Ustilago maydis cells to clastogens, a great increase in viability was observed if the treated cells were kept under starvation conditions. This restitution of viability is based on cell multiplication at the expense of the intracellular compounds freed from the damaged cells. Analysis of the effect of the leaked material on the growth of undamaged cells revealed opposing biological activity, indicating that U. maydis must possess cellular mechanisms involved not only in reabsorption of the released compounds from external environment but also in contending with their treatment-induced toxicity. From a screen for mutants defective in the restitution of viability, we identified four genes (adr1, did4, kel1, tbp1) that contribute to the process. The mutants in did4, kel1, tbp1 exhibited sensitivity to different genotoxic agents implying that the gene products are in some overlapping fashion involved in the protection of genome integrity. The genetic determinants identified by our analysis have already been known to play roles in growth regulation, protein turnover, cytoskeleton structure, and transcription. We discuss ecological and evolutionary implications of these results.